Epidemiology of National Collegiate Athletic Association men's and women's tennis injuries, 2009/2010–2014/2015. Issue 19 (30th December 2015) - Lynall, Robert C; Kerr, Zachary Y; Djoko, Aristarque; Pluim, Babette M; Hainline, Brian; Dompier, Thomas P
Abstract : Background: This study describes the epidemiology of men's and women's tennis injuries reported by the National Collegiate Athletic Association (NCAA) Injury Surveillance Program (ISP) during the 2009/2010–2014/2015 academic years. Methods: Injuries and athlete-exposure (AE) data originated from 19 varsity men's programmes (38 team-seasons); women's tennis data originated from 25 varsity programmes (52 team-seasons). Injury rates, injury rate ratios (IRRs) and injury proportions ratios (IPRs) were reported with 95% CIs. Results: The ISP captured 181 and 227 injuries for men's and women's tennis, respectively, for injury rates of 4.89 and 4.88/1000 AE for men and women, respectively. There were 32.2% and 63.9% reductions in men's and women's tennis practice injury rates between 2009/2010–2011/2012 and 2012/2013–2014/2015, but no reductions in competition injury rates. Competition injury rates were higher than practice injury rates in men's (IRR=2.32; 95% CI 1.72 to 3.13) and women's tennis (IRR=1.77; 95% CI 1.35 to 2.33). Most injuries in men's and women's tennis occurred to the lower extremities (47.0% and 52.4%, respectively), compared with the trunk (16.6% and 17.6%, respectively) and upper extremities (23.8 and 23.8, respectively). Conclusions: Injury rates in NCAA men's and women's tennis were similar overall. Practice injury rates in men's and women's tennis have declined, although competition rates have not changed. These findings may help inform injury prevention programmes in the future.